Structure of PSI, PSII and antennae complexes from yellow-green alga Xanthonema debile - Gardian, Zdenko; Tichý, Josef; Vácha, František (Photosynthesis research, 2011)
Photosynthetic carbon fixation by Chromophytes is one of the significant components of a carbon cycle on the Earth. Their photosynthetic apparatus is different in pigment composition from that of green plants and algae. In this work we report structural maps of photosystem I, photosystem II and light harvesting antenna complexes isolated from a soil chromophytic alga Xanthonema debile (class Xanthophyceae). Electron microscopy of negatively stained preparations followed by single particle analysis revealed that the overall structure of Xanthophytes' PSI and PSII complexes is similar to that known from higher plants or algae. Averaged top-view projections of Xanthophytes' light harvesting antenna complexes (XLH) showed two groups of particles. Smaller ones that correspond to a trimeric form of XLH, bigger particles resemble higher oligomeric form of XLH.
Keywords: Microscopy, Electron; Thylakoids; vysokoúčinná kapalinová chromatografie; fotosystém I (proteinový komplex); Photosynthesis; Stramenopiles; tylakoidy; Photosystem II Protein Complex; Light-Harvesting Protein Complexes; fotosyntéza; fluorescenční spektrometrie; elektronová mikroskopie; půdní mikrobiologie; fotosystém II (proteinový komplex); chlorofyl; Protein Multimerization; Chromatography, High Pressure Liquid; Soil Microbiology; Heterokontophyta; multimerizace proteinu; světlosběrné proteinové komplexy; Soil; půda; Spectrometry, Fluorescence; Chlorophyll; Photosystem I Protein Complex